Selection of Manipulator Configuration for a Portable Robot for Special Tasks - Krakówka, Tomasz; Typiak, Andrzej; Cader, Maciej (Journal of Automation, Mobile Robotics and Intelligent Systems, 2023)
This paper presents method of selection of configuration for manipulators of portable robots for special purposes. On the example of the portable PIAP Patrol robot, the analysis of tasks and related requirements for the functionality of the manipulator was presented. With the use of multi-criteria optimization tools, the selection of the manipulator configuration parameters was carried out, which leads to the maximization of selected working capacities while ensuring that the imposed requirements and mass and kinematic limitations are met. The results of simulation tests were presented and the scope of further work was outlined.